2015
DOI: 10.25103/jestr.085.16
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Sliding Mode Control Design of a SCARA Robot Manipulator System Under Parametric Variations

Abstract: The sliding mode control (SMC) has yet proven its efficiency through several theoretical researches. Indeed, the robotic field is recognized as one of the main SMC portals on practical implementations. The interest of this work consists in testing the SMC robustness and its reliability versus the parameters variation and model uncertainties. In this paper, an algorithm for trajectory tracking task of robot manipulators based on a SMC has been proposed. Then, aiming to deal with the presence of disturbances and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…A 5-DOF SCARA redundant manipulator model was tested using fuzzy nonlinear controllers [8]. An adaptive trajectory tracking algorithm was investigated using a sliding mode control (SMC) to subject disturbances and parametric uncertainties [9]. Mamdani-based fuzzy controller was established based on the Lagrange Euler dynamic model [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A 5-DOF SCARA redundant manipulator model was tested using fuzzy nonlinear controllers [8]. An adaptive trajectory tracking algorithm was investigated using a sliding mode control (SMC) to subject disturbances and parametric uncertainties [9]. Mamdani-based fuzzy controller was established based on the Lagrange Euler dynamic model [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These cause the measurement of system to be tedious and designing a control law to be of more difficulty. Convergence of the system state to the requested state will require a high-level control law (Adelhedi, Jribi, Bouteraa, & Derbel, 2015). An idealized controller may be implemented to achieve good performance when the dynamics of the system is perfectly known.…”
Section: Chapter 2: Literature Reviewmentioning
confidence: 99%
“…Adelhedi et al in (Adelhedi, Jribi, Bouteraa, & Derbel, 2015) for the control of SCARA robot with 3 DOF. Owing to the quality of adaptive systems to deal with parameter uncertainties, the authors have assumed the mass of third link to be unknown.…”
Section: Control Of Scara Robotmentioning
confidence: 99%
“…Another adaptive SMC was used for a SCARA industrial robot which revealed more accurate position tracking performance and better robustness in dealing with the model uncertainties than the classic SMC. 158 A planar 2-DOF robot was controlled by a novel adaptive SMC scheme which showed its effectiveness for the system trajectory tracking. 159,160 And also a constrained 2-DOF robot was controlled by an adaptive SMC technique in ref.…”
Section: Sliding Mode Controllersmentioning
confidence: 99%